2017
DOI: 10.1086/689908
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular effect of insulin in a rodent model of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is associated with metabolic derangements including insulin resistance, although their effects on the cardiopulmonary disease are unclear. We hypothesized that insulin resistance promotes pulmonary hypertension (PH) development and mutations in type 2 bone morphogenetic protein receptor (BMPR2) cause cellular insulin resistance. Using a BMPR2 transgenic murine model of PAH and two models of inducible diabetes mellitus, we explored the impact of hyperglycemia and/or hyperin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 41 publications
0
30
0
1
Order By: Relevance
“…5 Our group recently showed that the pulmonary vascular response to WD is driven by hyperinsulinemia rather than hyperglycemia. 6 Although the focus of the present work was to assess the effects of WD on RV structure and function, we observed a 39% increase in invasively measured RVSP in wild-type mouse without any other PH-promoting intervention. Moreover, this WD-induced increase in RVSP was reduced with metformin therapy.…”
Section: Discussionmentioning
confidence: 67%
“…5 Our group recently showed that the pulmonary vascular response to WD is driven by hyperinsulinemia rather than hyperglycemia. 6 Although the focus of the present work was to assess the effects of WD on RV structure and function, we observed a 39% increase in invasively measured RVSP in wild-type mouse without any other PH-promoting intervention. Moreover, this WD-induced increase in RVSP was reduced with metformin therapy.…”
Section: Discussionmentioning
confidence: 67%
“…An imbalance in prostacyclin production through arachidonic acid metabolism is long described in PAH and may be at least in part affected by alterations in lipid metabolism related to IR (38). As prior work by our group and others has suggested that IR is causal in the development of pulmonary vascular disease (10,11,13,14), we sought to define biological relevance of our lipid-related findings. We explored lipoprotein-related inflammation as a link between our plasma findings and pulmonary vascular disease.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 98%
“…Thus, lipoprotein IR is indicated by elevated VLDL (triglyceride)/HDL cholesterol ratio. IR is increasingly implicated in PAH; several rodent models of IR such as the ApoE -/mouse have pulmonary hypertension (10)(11)(12) and IR is an early feature of a transgenic rodent model of heritable PAH with BMPR2 mutation (13,14). In addition to atherogenic dyslipidemia, IR in the lipid axis is characterized by abnormal skeletal muscle lipid deposition (15)(16)(17).…”
mentioning
confidence: 99%
“…Further, even rodents without BMPR2 mutation develop mild elevations in pulmonary arterial pressure. In both the BMPR2 R899X mice and wild type controls, pulmonary arterial pressure was directly correlated with plasma insulin levels but not plasma glucose levels (Trammell et al, ). These data provide further evidence of a causal relationship between insulin resistance and PAH development.…”
Section: Metabolic Syndromementioning
confidence: 99%